Seeking the Indian Social Space - Mathieu Ferry; Jules Naudet; Olivier Roueff (South Asia Multidisciplinary Academic Journal)
This article takes as its specific starting point the idea that the Indian society constitutes a relational space, marked by the interdependency of various sub-spaces. It more precisely aims at producing a synthetic representation of the Indian social space. In order to do so, we draw upon the 2011-2012 data from the “Household Consumer Expenditure” survey of the National Sample Survey Office. The analysis leads us to produce a multidimensional typology of consumption and position profiles around which the households who make up the Indian social space are aggregated. Finally, we propose a summary figure of the principles that organize the Indian social space and the nine categories that comprise it. In the conclusion of the article, we discuss how this multidimensional approach to Indian society encourages to question prenotions like those of “middle class”, “two-tier India”, “urban-rural cleavage”, or ideas drawn from politico-bureaucratic language like “poverty threshold”.